Determinants of Socio-Demographic and Environmental Factors in Helicobacter Pylori Infection - Hanif, Ihsan; Tamtomo, Didik Gunawan; Murti, Bhisma (Indonesian Journal of Medicine, 2024)
Background: Helicobacter pylori (H. pylori) infection ranks as one of most frequent human infections in the world. This study aimed to investigate the determinants of H. pylori infection in patients at Universitas Sebelas Maret Hospital. Sebjects and Method: This was an analytic observational with a cross-sectional design. The study was conducted at Universitas Sebelas Maret Hospital, Sukoharjo, Central Java, from November to Desember 2023. A sample of 199 patients was selected for  this  study  by  fixed  disease  sampling.  The  dependent  variable  was H. pylori infection. The independent variables were number of household members, source of water, toilet type, education level, family income, eating habits, smoking status, region type, and waste disposal.  The  data  were  taken  via surveys with questionairre.  Multiple logistic regression was employed for data analysis. Results: The risk of H. pylori infection increased with number of households member ≥5 (AOR= 4.52; 95% CI= 1.78 to 11.45; p = 0.001), water source from well (AOR= 3.74; 95% CI= 1.54 to 9.08; p = 0.003), habits of eating by bare hand (AOR= 4.71; 95% CI= 1.98 to 11.20; p= 0 < 0.001), smoking (AOR= 2.68; 95% CI= 1.11 to 6.49; p = 0.028), and living in urban area (AOR= 2.94; 95% CI= 1.10 to 7.80; p = 0.030). Meanwhile, it also decreased with having education level ≥ high school (AOR= 0.24; 95% CI= 0.10 to 0.57; p < 0.001), having family income ≥ 2,200,000 (AOR= 0.15; 95% CI= 0.06 to 0.37; p < 0.001), and implementing waste disposal system with collected by staff (AOR= 0.26; 95% CI= 0.10 to 0.65; p = 0.004). Conclusion: The risk of H. pylori infection is determined by number of household members, source of water, education level, family income, eating habits, smoking status, region type, and waste disposal. Keywords: determinants, environmental, helicobacter pylori, socio-demographic